The Global local planes of English needs in Indonesian contexts - Manara, Christine (Register Journal, 2019)
ABSTRACTThis article reports one part of a larger study, exploring the global and local English needs in nine secondary level schools in several Indonesian contexts (i.e. Sumatera, Sulawesi, and East Nusa Tenggara). The study investigates: 1) teachers and students perceived understanding of the existence of English in their local contexts; 2) opinions of their current local and global needs of English in today’s globalized era; and 3) their opinion on the teaching and learning of English. Data were collected from questionnaires and interviews. The results show that students in different contexts have slightly different views and perceptions of English use and how it needs to be learned and taught for their current and future needs of English. Although slightly different in their perceptions of needs, there seems to be a coordinated understanding of English needs between the students and teachers. The findings also indicate that there is a growing awareness of the need to teach the communicative aspects of English in relation to students’ activities online. Therefore, the teaching of English needs to be conducted by providing more English exposure, integrating blended learning, adopting English for Specific Purposes approach, and teaching pragmatics knowledge and intercultural skills.